Horizontal recursion in soft OR. Issue 1 (2nd January 2019) - Smith, Chris M.; Shaw, Duncan
Abstract: In operational research (OR), the concept of recursion explains particular relationships between modelled systems. It clarifies how the same system properties are replicated vertically across hierarchically interdependent units, meaning these units should be amenable to the same analytical conventions. OR views recursion as hierarchical and therefore does not consider these properties in a horizontal sense. This paper uses theory from other disciplines to develop criteria that define recursive modelling for soft OR as vertical or horizontal. Empirical data was captured using WASAN to improve efficiency in a police force customer contact department. Four units were modelled using WASAN, and additional analysis using recursion was conducted to understand the horizontal interdependence across these four units. Feedback from participants suggests the horizontal recursion analysis provided valuable insights beyond that of individual models.